A Study Of Entrepreneurs' Characteristics, Management Skills, Marketing Strategies And Business Performance Among Multimedia Related Small Businesses - Gan , Geok Chew (2000)
The aim of this study was to examine the co-relationship between entrepreneurs' characteristics, management skills, marketing strategies and business performance of multimedia related small businesses in Melaka, Malaysia. Based on previous empirical findings and theoretical literature, a new research framework was established to illustrate the proposed correlation between variables, and hypotheses were developed to test the proposed correlation. One hundred and thirty companies were selected to test the proposed correlation. One hundred and thirty companies were selected from the list of companies furnished by the Department of Business Registration. These companies have less than 75 employees with yearly turnover not exceeding 10 million Ringgit Malaysia. Data were obtained by self-administrated questionnaire from owners/managers of the companies. Response rate was 76.92% ( 100 out of 130 ). SPSS programme and Microsoft Excel were used to perform correlation test and t-test, respectively. There were few major findings in the study. Firstly, this study found that marketing strategies were important for entrepreneurs of multimedia business for their net profits (average monthly net profit before tax ) rather than to generate sales ( average monthly turnover ). Ten marketing strategies were significantly correlated to profit versus only two marketing strategies showed significant correlation with sales. This implies that entrepreneurs who aim to improve their profit should emphasise on market niche, product differentiation, service differentiation, advertising, sales promotion, personal selling, pricing, market penetration, market development and product development strategies. As to improve sales, only product differentiation and personal selling were perceived as helpful in this study context. Secondly, this study found that management skills were crucial for sales ( average monthly turnover ) than profit (average monthly net profit before tax). Eight management skills ( organising, leading, motivating, purchasing, training, communication, decision making and time management) that indicated significant correlation with profit. It was an interesting finding that management skills pertaining to people management were crucial for sales whereas management skills with relate to entrepreneuurs' self-competency and cost management were critical to profit. This implied that entrepreneurs should improve their organising, leading, motivating, training and communication skills if they wish to achieve higher sales. Whereas, to increase profit, entrepreneurs should enhance planning, risk management, decision-making and time management skills. Thirdly, for motivation to start up factors, it was found that "want to be own boss" as a pull factor and push factors like "frustration" and "no career advancement in previous job" were significantly correlated to net profit. Fourthly, personal traits were found not important when compared to marketing strategies and management skills. Only 5 out of 18 traits were correlated to net profit and they were ambitious, honesty, reliability, willingness to sacrifice and enthusiasm. Lastly, demographic factors like employment history and business experience were found to be least important to business performance among all other factors. Apart from these findings, "stiff competition" was the most cited issue encountered by entrepreneurs. Other common issues faced were customer service, people management and marketing of products/services.